Need a fast expert's response?
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
1/(x^2-2x)+x/(4-2x)=1/{x(x-2)}+x/{2(2-x)}=1/{x(x-2)}-x/{2(x-2)}={2-x^2}/(2x(x-2))
Yes i need to simplify it.
Do you need to simplify this expression?
^ square root and then 1/(x^2-2x) is a fraction
Comments
1/(x^2-2x)+x/(4-2x)=1/{x(x-2)}+x/{2(2-x)}=1/{x(x-2)}-x/{2(x-2)}={2-x^2}/(2x(x-2))
Yes i need to simplify it.
Do you need to simplify this expression?
^ square root and then 1/(x^2-2x) is a fraction
Leave a comment